Advances in Urban Ecology - Marina, Alberti (Springer, 2017)
To study urban ecosystems and test hypotheses about mechanisms that govern their dynamics, we need to detect and accurately quantify the urban landscape pattern and its change over time. In Chapter 4, I propose that hybrid landscapes in urbanizing regions have distinctive signatures and propose an approach to quantify them. Chapters 5 through 8 examine the impacts of urban patterns on the biophysical environment and the resulting effects on ecosystem dynamics. Throughout these chapters I explore the connections between human and ecological processes and their impli-cations for integrated research. Chapter 9 addresses the complexity and uncertainty in modeling urban ecosystems, their variability and dynamics, and the causes and effects of heterogeneity on ecological and economic processes at various scales.